Seguimiento de referencia en náhuatl - Peregrina LLanes, Manuel (2016)
The reference tracking is introduced from approach cognitive-functionalist and from a typological view to shed light on the mechanisms that this language uses to codify the reference and keep cohesion along the text. This study is about Nahuatl discourse. The analysis is based on Information Structure (IS) and Discursive Coherence. It is explored through the linguistic phenomenon named reference tracking.